Factores influyentes de los costos de producción en la rentabilidad, de la finca Juana Fernández de el Guabo, período 2016. - Calderon Porras, Miriam Del Rocio (2017)
This work of titling or case study, is based on the exhaustive analysis of the influential Factors of production costs in the profitability of the "Juana Fernandez" Canton El Guabo farm for 2015-2016 for comparison; Through the qualitative and quantitative analysis of the elements to establish the effects on profitability. This research was carried out with the support of the bibliographical references, being of great help, because it is based on authors who defend the theory being supported by its information, giving greater ease to the future investigators who carry out their case study based on this information. We also have the field research that was carried out within the farm, for which its owner provided us with the necessary information to carry out the methodology, obtaining the results and, in turn, the conclusions, to give the respective recommendations. After defining and analyzing the problems that affect the company, mainly the production process; Such as inconsistency in cost reporting, inadequate control and accounting of materials, lack of real production costs. In order to carry out this research processing and analysis, it was carried out by searching for information that the Finca facilitated by providing the financial statements. This information was used as a basis for calculating the cost elements, where it was possible to compare the two periods, demonstrating that in the period 2015 were higher expenses, establishing that this period was not a good year, representing less gains and greater the costs. Contributing this analysis to a more adequate decision making, that provides less costs and more profits, where it was beneficial for the period 2016 where the costs were smaller. Also the application of the financial indicators of profitability was realized. Disclosing the turnover of assets, sales, profits and equity, demonstrating that the profitability was lower in the period 2016, although its costs decreased under its profitability. It is recommended to establish an adequate plan to control your production costs, conduct a detailed study at the field level and be able to establish why the costs increase or decrease. Always take into account the moment of increase or decrease of the official price per box of banana q is not stable, thus avoiding adverse effects that affect the economy of the company. It also gives a pattern to improve in the coming periods and not incur the same flaws, which affect the economy of the Finca, for that reason owners must take very into account the recommendations q this analysis is detailed, which is done After knowing the results, obtaining the conclusions where the failures existed, to start from there and to carry out a more exhaustive study gathering more information, serving as support to make the respective changes that improve the productive process and in turn increase the profitability and increase the earnings. Helping this to keep the economy of the company at a good level, being beneficial, both for the owners of the farm and for the workers. The Finca "Juana Fernández" after this analysis, will be able to make new decisions for improvements of the same, hoping to be of great benefit for her, the investigation that has been carried out, counting on her help in giving us the information necessary to carry out this study.